1999
DOI: 10.1021/jf9809028
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Straight-Chain Ester Volatiles in Red Delicious and Granny Smith Apples Using Deuterium-Labeled Precursors

Abstract: Biosynthesis of straight-chain ester volatiles by Granny Smith and Red Delicious apples was investigated using deuterium-labeled fatty acids, C-6 aldehydes, and alcohols. Perdeuterated saturated and monounsaturated fatty acids were metabolized to hexyl-d(11), hexanoate-d(11), heptanoate-d(13), and octanoate-d(15) esters, whereas perdeuterated linoleic acid produced only hexyl-d(11) and hexanoate-d(11) esters. Exposure of fruit to vapors of deuterated 3Z-hexenal, 2E-hexenal, and hexanal identified the following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
129
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(139 citation statements)
references
References 40 publications
9
129
0
1
Order By: Relevance
“…Ripening-related gene sets included genes regulated by the MADS-BOX transcription factor family 29,30 , SEPALLATA transcription factor family, and ethylene-related genes such as ACS (aminocyclopropane-1-carboxylic acid synthase), a key ethylene-production enzyme involved in ripening 31 . Other upregulated processes related to taste and odor included triterpenoid metabolism, which has been associated with the intensely bitter taste of Ganoderma lucidum (Lingzhi) 32 , and lipid-related genes involved in the production of C 6 volatile compounds (hexanal and hexanol), which have been associated with the green odor profiles of apples, tomatoes, and bananas, as well as undesirable rancid odors when present at high levels 33,34 . Conversely, processes enriched in non-fruit organs included photosynthetic pathways and the regulation of nitrogen metabolism, likely required by roots and leaves to manufacture amino acids.…”
Section: A R T I C L E Smentioning
confidence: 99%
“…Ripening-related gene sets included genes regulated by the MADS-BOX transcription factor family 29,30 , SEPALLATA transcription factor family, and ethylene-related genes such as ACS (aminocyclopropane-1-carboxylic acid synthase), a key ethylene-production enzyme involved in ripening 31 . Other upregulated processes related to taste and odor included triterpenoid metabolism, which has been associated with the intensely bitter taste of Ganoderma lucidum (Lingzhi) 32 , and lipid-related genes involved in the production of C 6 volatile compounds (hexanal and hexanol), which have been associated with the green odor profiles of apples, tomatoes, and bananas, as well as undesirable rancid odors when present at high levels 33,34 . Conversely, processes enriched in non-fruit organs included photosynthetic pathways and the regulation of nitrogen metabolism, likely required by roots and leaves to manufacture amino acids.…”
Section: A R T I C L E Smentioning
confidence: 99%
“…The major group of compounds produced from ripe fruit of apple cultivars, such as Royal Gala, is esters (Young et al, 1996(Young et al, , 2004, including straight-chain esters derived from fatty acids (Rowan et al, 1999) and branched-chain esters derived from branchedchain amino acids (Rowan et al, 1996). Of the straightchain esters, C-6 constituents are thought to be derived via the lipoxygenase pathway from linoleic acid (Fig.…”
Section: Flavor Biosynthesismentioning
confidence: 99%
“…Ester formation in apple is largely confined to the fruit tissue and, more specifically, the skin (Knee and Hatfield, 1981). It has been demonstrated that the LOX and b-oxidation pathways permit the catabolism of fatty acids during fruit ripening to supply precursors for ester formation (Rowan et al, 1999). Consequently, the expectation is that gene expression for some of the enzymes involved in these pathways will increase during ripening and/or be localized within fruit skin tissues.…”
Section: Analysis Of Genes Potentially Involved In Ester Biosynthesismentioning
confidence: 99%